Monitoring Oxygenation and Gas Exchange in Neonatal Intensive Care Units: Current Practice in the Netherlands - Tan, Ratna N. G. B.; Mulder, Estelle E. M.; Lopriore, Enrico; te Pas, Arjan B. (Frontiers in Pediatrics, 2015)
Background. Although recommendations in oxygenation and gas exchange monitoring in the neonatal intensive care unit (NICU) are available, little is known of the current practice. Aim. To evaluate the current practice in oxygenation and gas exchange monitoring of the NICUs in the Netherlands. Methods. An online survey-based questionnaire concerning preferences and current practice of monitoring oxygenation and gas exchange was sent out to all 107 neonatal staff members (neonatologists, neonatal fellows, physician assistants) of the 10 NICUs in the Netherlands. Results. The response rate was 42%. Pulse oximetry, partial pressure of oxygen in arterial blood gas (paO2) and oxygen saturation in arterial blood gas (saO2) was used by respectively 100%, 80% and 27% of the staff members for monitoring oxygenation. Of all staff members 76% considered pulse oximetry as the best parameter for monitoring oxygenation, 22% paO2 and 2% saO2. Blood gas, transcutaneous gas monitoring, endotracheal gas monitoring and near-infrared spectroscopy was used by respectively 100%, 82%, 40% and 18% of the staff members for monitoring gas exchange. During endotracheal ventilation, 67% of the caregivers would exclusively accept arterial blood gas for gas exchange monitoring. In contrast during non-invasive ventilation, 68% of the caregivers had no preference for arterial or capillary blood gas. Capillary blood gas is found reliable in infants with warm extremities by 76% of the caregivers. Venous blood gas would be accepted by 60% of the caregivers, independent of the mode of respiratory support and only when venous blood sample was needed for other reasons. Conclusion. This survey identified a wide variation in preference in monitoring oxygenation and gas exchange monitoring among Dutch neonatal staff members.